Brown Adipocyte-Specific PPARγ (Peroxisome Proliferator-Activated Receptor γ) Deletion Impairs Perivascular Adipose Tissue Development and Enhances Atherosclerosis in Mice. Issue 8 (August 2018) - Xiong, Wenhao; Zhao, Xiangjie; Villacorta, Luis; Rom, Oren; Garcia-Barrio, Minerva T.; Guo, Yanhong; Fan, Yanbo; Zhu, Tianqing; Zhang, Jifeng; Zeng, Rong; Chen, Y. Eugene; Jiang, Zhisheng; et al.
Abstract : Objective—: Perivascular adipose tissue (PVAT) contributes to vascular homeostasis by producing paracrine factors. Previously, we reported that selective deletion of PPARγ (peroxisome proliferator-activated receptor γ) in vascular smooth muscle cells resulted in concurrent loss of PVAT and enhanced atherosclerosis in mice. To address the causal relationship between loss of PVAT and atherosclerosis, we used BA-PPARγ-KO (brown adipocyte-specific PPARγ knockout) mice. Approach and Results—: Deletion of PPARγ in brown adipocytes did not affect PPARγ in white adipocytes or vascular smooth muscle cells or PPARα and PPARδ expression in brown adipocytes. However, development of PVAT and interscapular brown adipose tissue was remarkably impaired, associated with reduced expression of genes encoding lipogenic enzymes in the BA-PPARγ-KO mice. Thermogenesis in brown adipose tissue was significantly impaired with reduced expression of thermogenesis genes in brown adipose tissue and compensatory increase in subcutaneous and gonadal white adipose tissues. Remarkably, basal expression of inflammatory genes and macrophage infiltration in PVAT and brown adipose tissue were significantly increased in the BA-PPARγ-KO mice. BA-PPARγ-KO mice were crossbred with ApoE KO (apolipoprotein E knockout) mice to investigate the development of atherosclerosis. Flow cytometry analysis confirmed increased systemic and PVAT inflammation. Consequently, atherosclerotic lesions were significantly increased in mice with impaired PVAT development, thus indicating that the lack of normal PVAT is sufficient to drive increased atherosclerosis. Conclusions—: PPARγ is required for functional PVAT development. PPARγ deficiency in PVAT, while still expressed in vascular smooth muscle cell, enhances atherosclerosis and results in vascular and systemic inflammation, providing new insights on the specific roles of PVAT in atherosclerosis and cardiovascular disease at large. Abstract : Supplemental Digital Content is available in the text.